Chemical composition and antioxidant potential of Jaracatia spinosa and Vasconcellea quercifolia A. St-Hil and their use in food: a brief review (Research, Society and Development, 2021)
Brazil is recognized for its wealth of varieties of native plants and fruits. This review aims to evaluate research related to non-conventional plants and exotic fruits, directed to native fruits of Brazil. Among them, little is known about the Jaracatia spinosa and Vasconcela quercifolia fruits, known only regionally. Therefore, by searching with the descriptive ‘PANCs’; ‘Brazilian exotic fruits’, ‘Jaracatia spinosa’, ‘Vasconcella quercifolia’ in the Scielo, Science direct and Web of Science databases, articles that could concentrate information on their nutritional and biochemical composition were selected in order to expand knowledge about their properties. As for example, regarding dietary fiber content, for the two fruits studied, greater results were obtained than for papaya (Carica papaya) also belonging to the Cariaceae family, which values the importance of spreading the consumption of these other fruits nationwide and encourage their consumption and use.